Cold sensing in grapevine—Which signals are upstream of the microtubular “thermometer” - Wang, Lixin; Nick, Peter (Plant, cell and environment, 2017)
Plants can acquire freezing tolerance in response to cold but non‐freezing temperatures. To efficiently activate this cold acclimation, low temperature has to be sensed and processed swiftly, a process that is linked with a transient elimination of microtubules. Here, we address cold‐induced microtubules elimination in a grapevine cell line stably expressing a green fluorescent protein fusion of Arabidopsis TuB6, which allows to follow their response in vivo and to quantify this response by quantitative image analysis. We use time‐course studies with several specific pharmacological inhibitors and activators to dissect the signalling events acting upstream of microtubules elimination. We find that microtubules disappear within 30 min after the onset of cold stress. We provide evidence for roles of calcium influx, membrane rigidification, and activation of NAD(P)H oxidase as factors in signal susception and amplification. We further conclude that a G‐protein in concert with a phospholipase D convey the signal towards microtubules, whereas calmodulin seems to be not involved. Moreover, activation of jasmonate pathway in response to cold is required for an efficient microtubule response. We summarize our findings in a working model on a complex signalling hub at the membrane‐cytoskeleton interphase that assembles the susception, perception and early transduction of cold signals. Cold stress limits the agricultural use of many plants in temperate climate, including the cash crop grapevine. One of the early responses to cold stress is the elimination of microtubules. This microtubule response has been shown to be required to activate efficient adaptation to cold. In the current work, we dissect the early events of cold signalling upstream of microtubules using a transgenic grapevine cell line expressing a fluorescent tubulin marker. We find that calcium influx, membrane rigidification, and activation of NAD(P)H oxidase contribute to signalling, and that a G protein in concert with phospholipase D convey the signal towards microtubules, whereas calmodulin seems to be not involved. Moreover, cold‐induced activation of the jasmonate pathway is required for an efficient microtubule response. We summarize our findings in a working model on a complex signalling hub at the membrane‐cytoskeleton interphase that assembles the susception, perception, and early transduction of cold signals. These insights can be used in the future to design strategies targeted on improved cold tolerance, either by molecular‐assisted breeding, or, alternatively to genetic changes, by chemical manipulation of early signalling events in order to improve cold tolerance of cultivars which are otherwise cold‐sensitive in temperate climates.